Modulating Crystal and Interfacial Properties by W‐Gradient Doping for Highly Stable and Long Life Li‐Rich Layered Cathodes. (2nd February 2022) - Meng, Junxia; Xu, Lishuang; Ma, Quanxin; Yang, Mengqian; Fang, Yuzhong; Wan, Guangying; Li, Ruhong; Yuan, Jujun; Zhang, Xianke; Yu, Huajun; Liu, Lingli; Liu, Tiefeng
Abstract: Stabilizing Li‐rich layered oxides without capacity/voltage fade upon cycling is a prerequisite for a successful commercialization. Although the inhibition of structural and interfacial changes is identified as an effective strategy, the battery community always seeks for a technologically flexible method to make it really competitive among the cathode. Herein, the gradient W‐doping within Li1.2 Mn0.56 Ni0.16 Co0.08 O2 (LLMO) is proposed to relieve crystal disintegration and simultaneously enhance interfacial stability because of the formation of Li2 WO4 coating layer on the material surface. This is mainly attributed to the scenario that partial Mn replacement by W can stabilize the LLMO structure and regulate the electrochemical activity of Mn element. The W‐doped LLMO (W@LLMO) possesses improved specific capacity and voltage stability (83.2% capacity retention and voltage retention of 94.9% after 200 cycles at 0.5 C). Besides, a practical pouch cell based on the W@LLMO cathode presents sufficient gravimetric energy density (318 Wh kg −1 ) and cycling stability (capacity retention of 87.7% after 500 cycles at 1.0 C). This study presents an effective method to design robust Li‐rich layered cathodes for next‐generation Li‐ion batteries. Abstract : The W‐doped Li1.2 Mn0.56 Ni0.16 Co0.08 O2 (W@LLMO) cathode materials are successfully regulated through a W‐gradient doping method and finally exhibit a long‐term cycling of the W@LLMO/G pouch cell.